Principle of Adaptive Micro-Processor Current Directional Protection of Line - F. A. Romaniuk; A. A. Tishechkine; O. A. Gurjanchik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper studies one of the principles used for execution of adaptive micro-processor current directional protection of a line against inter-phase short circuits. This principle makes it possible to decrease a number of measuring elements of protection current and increase protection-ability while preserving high speed of response.